Genetic variation in Mycobacterium tuberculosis isolates from a London outbreak associated with isoniazid resistance. Issue 1 (December 2016) - Satta, Giovanni; Witney, Adam; Shorten, Robert; Karlikowska, Magdalena; Lipman, Marc; McHugh, Timothy
Abstract Background The largest outbreak of isoniazid-resistant (INH-R)Mycobacterium tuberculosis in Western Europe is centred in North London, with over 400 cases diagnosed since 1995. In the current study, we evaluated the genetic variation in a subset of clinical samples from the outbreak with the hypothesis that these isolates have unique biological characteristics that have served to prolong the outbreak. Methods Fitness assays, mutation rate estimation, and whole-genome sequencing were performed to test for selective advantage and compensatory mutations. Results This detailed analysis of the genetic variation of these INH-R samples suggests that this outbreak consists of successful, closely related, circulating strains with heterogeneous resistance profiles and little or no associated fitness cost or impact on their mutation rate. Conclusions Specific deletions and SNPs could be a peculiar feature of these INH-RM. tuberculosis isolates, and could potentially explain their persistence over the years.